The impact of innovation and gratification on authentic experience, subjective well-being, and behavioral intention in tourism virtual reality: The moderating role of technology readiness - Kim, Myung Ja; Lee, Choong-Ki; Preis, Michael W. (Telematics and informatics, 2020)
•The importance of virtual reality (VR) is growing rapidly in tourism-related areas.•This study develops a model incorporating innovation and gratification theories.•Innovation and gratification theories explain why consumers participate in VR.•Authentic experience and well-being mediate consumer behavior on VR tourism.•Technology readiness moderates the relationship between well-being and intention. Despite the increasing amount of attention paid to virtual reality (VR) tourism and the rising importance of VR tourism, a theoretically integrated model of behavior has not been developed. To fill this void, we build and test a framework based on both innovation diffusion and uses and gratifications theories to explain why people participate in VR tourism. The moderating role of VR tourists’ technology readiness (optimism and innovativeness) between subjective well-being and behavioral intention is also examined. Results demonstrate that authentic experience and subjective well-being are affected by simplicity, benefit, compatibility (attributes of innovation diffusion), informativeness, social interactivity, and playfulness (uses and gratifications attributes). Behavioral intention is more positively influenced by subjective well-being than by authentic experience. The moderating role of technology readiness between subjective well-being and behavioral intention is stronger in individuals with high optimism and innovativeness than their counterparts with low optimism and innovativeness.